Transformation of educational practices in the conditions of the digital environment - Natalia V. Ageenko; Elena A. Barashkina; Natalia A. Maslenkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The generation gap in education is appeared when people of the non-digital generation teach the representatives of the digital age. Modern education, based on practices developed in the written culture, continues to be based on reading, which remains the key, necessary skill for the time being. But the digital generation requires a change in educational traditions, disciplinary (normalizing) paradigms - basic skills, appropriate training technologies. In this article, higher education institutions act as a field of research. The authors identify several mechanisms of disciplinary power working in the educational environment and experiencing a significant transformation in the transition from traditional book culture to digital one. It is concluded that there is a need to redistribute the normalizing functions between the teacher and the student, change the type of activity of both subjects of educational activity; working out of new training formats are actualized.